2019
DOI: 10.1002/jat.3829
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark dose estimation of urinary and blood cadmium as biomarkers of renal dysfunction among 40‐75‐year‐old non‐smoking women in rural areas of southwest China

Abstract: This study evaluated the association between urinary cadmium (U‐Cd) and blood Cd (B‐Cd) and several biomarkers of renal dysfunction (α1‐microglobulin [α1‐MG], β2‐microglobulin [β2‐MG], N‐acetyl‐β‐d‐glucosaminidase, metallothionein, retinol‐binding protein and microalbumin [mALB]) and identified the biomarker(s) that was most closely correlated with U‐Cd and B‐Cd among female residents in rural areas of southwest China. U‐Cd, creatinine (Cr), B‐Cd and the above‐mentioned six biomarkers in morning spot urine sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 68 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Females were more sensitive to Cd accumulation than males and in the long-term β 2 -MG was a better biomarker of tubular damage than NAG. In the recent benchmark dose estimation study 65 it was found urinary β 2 -MG and tubular albuminuria were also good biomarkers to assess the nephrotoxic effects of long-term environmental Cd exposures in Chinese women.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Females were more sensitive to Cd accumulation than males and in the long-term β 2 -MG was a better biomarker of tubular damage than NAG. In the recent benchmark dose estimation study 65 it was found urinary β 2 -MG and tubular albuminuria were also good biomarkers to assess the nephrotoxic effects of long-term environmental Cd exposures in Chinese women.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…In addition, Cd has a very high affinity for the isolated ER, and in vitro , Cd also blocks the binding of estrogen to its receptor, thereby interfering with the regulatory effects of estrogen on bone metabolism ( 38 ). Other theories include that cadmium causes renal dysfunction through damage to renal tubular epithelial cells, which diminishes calcium reabsorption by renal tubular cells and impedes calcium absorption from the digestive tract ( 39 , 40 ). Besides, cadmium exposure interferes with parathyroid hormone (PTH), which affects the production of active vitamin D, further leading to bone loss ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent evaluation by the International Union on Pure and Applied Chemistry (IUPAC) estimated a LOAEL for renal dysfunction of 2 nmol/mmol Cr (2 μg/g Cr) [ 29 ]. A study in China explored U-Cd limits in a polluted area in southwest China and determined BMDL 5 to be 3.48 μg/g Cr [ 30 ]. The BMDL 5 of U-Cd based on β 2 -MG in non-polluted areas in Zhejiang, China, was calculated to be 0.62–0.64 μg/g Cr [ 31 ].…”
Section: Discussionmentioning
confidence: 99%